Food for Africa The life and work of a scientist in GM crops - Thomson, Jennifer (UCT Press, 2013)
Jennifer Thomson, one of the world's leading scientific advisors on genetic engineering, traces through anecdote and science the development of a hotly contended area of research, from the dawn of genetic engineering in the USA in 1974, through the early stages of its uptake in South Africa to the current situation in which approximately 80% of maize in South Africa is genetically modified for drought resistance. Through her own story of how she came to choose GM as a career and her path-breaking involvement in the development of GM research, she describes the spread of this technology into other parts of Africa and her venture into unknown territory to develop crops resistant to drought, insects and viruses, a journey in which she came up against the multinational Monsanto. The book describes a remarkable personal and scientific evolution and looks to a future in which staple crops may be grown in difficult conditions by smallholder farmers and help Africans achieve food security.